Pengaruh Varietas Jahe (Zingiber officinale) terhadap Karakteristik Minuman Serbuk Empon-Empon - Lina Herlinawati; Ida Ningrumsari; Asep Hodijat (University of Insan Cendekia Mandiri, 2023)
The research on making empon-empon microcrystals is expected to make it easier for people to consume healthy drinks because of their more practical. This study also aims to determine the effect of ginger varieties used in the manufacture of empon-empon microcrystals on water content, total dissolved solids, and hedonic tests on taste, color, aroma, and aftertaste. The experimental design that will be used in this study is a Completely Randomized Design (CRD) with one variable consisting of three levels, namely ginger varieties (big ginger, red ginger, and small ginger). The experiment was repeated 6 times, so 18 experimental units were obtained. Determination of the best sample using the scoring method. The best samples were analyzed for total sugar content and antioxidant activity using UV Visible spectrophotometer DPPH method. The results showed that the different varieties of ginger had a significant effect on the aroma, taste, and aftertaste of the empon-empon powder drink. Differences in ginger varieties had no significant effect on the color, water content, and total dissolved solids of empon-empon powder drink. The best sample was the empon-empon powder drink using ginger emprit which had a reducing sugar content of 1.3133%, disaccharide content of 63.2125%, a total sugar content of 64.5258%, IC50 value for antioxidant activity of 78.01 µg/mg, the water content of 3.90%, total dissolved solids was 67.85%, the color attribute preference test value was 4.30, the aroma was 2.50, the taste was 3.92, and the aftertaste was 3.81.